Aktualne tendencje w wyborze formy kształcenia uczniów z uszkodzonym słuchem w obecnym systemie oświatowym w Polsce - Olempska-Wysocka, Magdalena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The aim of this article is to present changes in the education of deaf and hard of hearing persons over the last 7 years. The trends in the education of children with hearing impairment clearly point to the departure from special forms of education in favour of public education and integration. These changes, however, are a challenge for both teachers, parents and students with hearing impairment.